Deliberate Self-Indulgence Versus Involuntary Loss of Self-Control: Toward a Robust Cross-Cultural Consumer Impulsiveness Scale - Sharma, Piyush; Sivakumaran, B.; Marshall, R. (Routledge, 2011)
There is neither a consensus about the dimensionality of the consumer impulsiveness construct nor sufficient evidence about the validity and cross-cultural measurement equivalence of its various scales. We address these gaps by using cross-cultural differences in control orientations as the conceptual foundation for a more robust consumer impulsiveness scale. Specifically, we demonstrate that unlike individualistic consumers, collectivistic consumers distinguish between deliberate self-indulgence and involuntary loss of self-control, as reflected in the three-factor structure (prudence, self-indulgence, and self-control) for the collectivists and a two-factor structure (prudence and hedonism) for the individualists. We also discuss some implications and limitations of this research.